OPTIMIZATION OF TRANSPORTATION OF WOODWORKING IN-DUSTRY PRODUCTS - Sazonets, O. (Systems and Technologies, 2021)
The article considers the legal framework for regulating functioning of the woodworking industry. The negative consequences of staff reductions at enterprises are pointed out. It is mentioned that more and more woodworking en-terprises often complain about problems with the supply of resources due to transport inconsistencies. Ukrainian entrepreneurs are concerned not only with the supply of raw materials, but also with how the products will be delivered to the consumer. The efficiency of use of production by consumers depends on it. This task optimizes transport costs, considering the preferences of wood in-dustry producers for a particular mode of transport. This type of industry can func-tion effectively only if the logistics of supply of both raw materials and intermediate and finished products that provide transport in Ukraine can be successful. Analyz-ing logging technologies, scientists have found that a single-stage transport scheme is used to transport about 80% of products. This scheme is relevant for a short dis-tance of export. Also, about 20% of timber is exported under a multi-stage transport scheme.As a part of the woodworking industry, certain groups of industries have been identified. It is noted that the enterprises of the woodworking industry produce mainly goods of national consumption. However, the significant part of woodwork-ing products is consumed in other industries in the national economy, so timely de-livery of products to places of consumption is very important.The article conducts research and identifies two main types of transportation of wood products, namely, by automobiles and rail. The advantages and disad-vantages of using these modes of transport are presented. An algorithm for the se-lection of these tools by the transport department of the woodworking company has been developed. A model is constructed using the method of optimization of the utility function and constraints in the form of a linear function. The problem is solved using the method of Lagrange multipliers. The proportions of the company's use of road and rail transport in the supply of products are calculated.